2014
DOI: 10.1590/1983-084x/12_180
|View full text |Cite
|
Sign up to set email alerts
|

Teor e composição do óleo essencial de quatro acessos e duas cultivares de manjericão (Ocimum basilicum L.)

Abstract: RESUMO:O objetivo desse estudo foi avaliar o teor e a composição química dos óleos essenciais de quatro acessos silvestres de manjericão (Ocimum basilicum L.), provenientes de diferentes regiões geográficas, e duas cultivares comerciais cultivados sob as mesmas condições edafoclimáticas. As sementes dos acessos foram coletadas nos município de Gurupi-TO (GUR) e de Monte Alegre-GO (MAL, MVE e FPS) e as sementes da cultivar comercial manjericão roxo (MR) foram adquiridas no comércio de Gurupi e da cultivar Maria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…The characterization of the chemical composition of the essential oils of plants of the same species allows generating information for the obtainment of the most suitable plants for therapeutic use, and for the obtainment of plants with higher essential oil content, allowing selection and insertion in genetic improvement programs (VELOSO et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characterization of the chemical composition of the essential oils of plants of the same species allows generating information for the obtainment of the most suitable plants for therapeutic use, and for the obtainment of plants with higher essential oil content, allowing selection and insertion in genetic improvement programs (VELOSO et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found great chemical diversity in the essential oil of medicinal and aromatic species, such as Ocimum basilicum L. (VELOSO et al, 2014;COSTA et al, 2015), Lippia alba (Mill.) N. E. Brown (NETO et al, 2012;BLANK et al, 2015), Varronia curassavica Jacq.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Ocimum basilicum L., it is a plant belonging to the Lamiaceae family and is widely used by traditional medicine, mainly due to its essential oils, with methyl chavicol, linalool, geranial and estragol as the major constituents (Veloso et al, 2014).…”
Section: Species Mentioned For the Treatment Of Symptoms And/or Pathomentioning
confidence: 99%
“…Este fato indica a possibilidade de outros compostos serem responsáveis pela atividade larvicida do óleo essencial ou ainda a existência de um sinergismo entre o linalol e os demais constituintes. Os fenilpropanoides presentes no óleo essencial do manjericão apresentam funções importantes na defesa química do vegetal contra pragas, predadores e patógenos (VELOSO et al, 2014).…”
Section: éPocas De Amostragem (Horas Após Inicio Do Experimentounclassified